Late effects of mass acute phosphine poisoning - Case report - Małgorzata Waszkowska; Jolanta Walusiak-Skorupa; Dorota Merecz-Kot; Marta Wiszniewska (Nofer Institute of Occupational Medicine, 2018)
This paper reports the case of collective acute phosphide (PH 3 ) intoxication among the crew aboard a merchant ship. All the intoxicated individuals were hospitalized 3 months after the accident. The aim of examinations was to identify late health effects of the accident. Laboratory tests and consultations were performed during their stay in the hospital. There were 5 cases of toxic liver damage. other 5 patients were diagnosed with posttraumatic stress disorder and adjustment disorders. The results of the study suggest that in cases of acute phosphide intoxication, the assessment of patients' psychological functioning should be an indispensable part of diagnostic procedure. Med Pr 2018;69(3):337-344